A novel 'surgeon-dominated' approach to the design of 3D-printed patient-specific surgical plates in mandibular reconstruction: a proof-of-concept study. Issue 1 (January 2020) - Yang, W.-f.; Zhang, C.-y.; Choi, W.S.; Zhu, W.-y.; Li, D.T.S.; Chen, X.-s.; Du, R.; Su, Y.-x.
Abstract: Three-dimensionally (3D) printed patient-specific surgical plates have been proposed to facilitate mandibular reconstruction and are attracting extensive attention. We have recently reported the high accuracy of 3D-printed patient-specific surgical plates used in head and neck reconstruction. Based on this previous work, the current study proposes a novel 'surgeon-dominated' approach to the design of 3D-printed patient-specific surgical plates. The aim of this proof-of-concept study was to explore the workflow and technical procedures of the surgeon-dominated approach. The workflow includes virtual surgery, the design and printing of patient-specific surgical devices, and real surgery. The prototype of the patient-specific surgical plate was designed by surgeons and further optimized for 3D printing by engineers. Different types of mandibular defect were tested to confirm the wide applicability of this approach. Cases in which this approach was used were reviewed and the duration of time spent on each case studied. Based on a total of 16 patients, the time spent on virtual surgery and plate design was 18.83 ± 13.19 hours, and the time taken for 3D printing, post-processing, and product delivery was 162.9 ± 55.15 hours. Therefore, this novel surgeon-dominated approach is feasible and time-saving, which would likely promote the wide application of patient-specific surgical plates and lead to a new era of 'digitization and precision' in mandibular reconstruction. ClinicalTrials.gov registration: NCT03057223.